2020
DOI: 10.1039/d0na00409j
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin heavy-metal-free ZnTe nanoplatelets formed from magic-size nanoclusters

Abstract: Atomically thin colloidal quasi-two-dimensional (2D) semiconductor nanoplatelets (NPLs) have attracted tremendous attention due to their excellent properties and stimulating applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In conclusion, as a representative candidate of the class of 2D materials, colloidal CdSe NPLs constitute a significant platform for the fundamental research and development of the next generation of optical devices. Knowledge of the spectral tunability and self‐assembly methods of CdSe NPLs could facilitate the research of other novel cadmium‐free solution‐processed 2D materials such as ZnTe, [ 165 ] ZnSe, [ 166 ] HgTe, [ 116 ] and ZnS [ 167 ] NPLs. For example, the emission peak wavelength has been tuned discretely from 345 to 380 nm in the case of ZnSe NPLs by modulating the vertical thickness over the NPL ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, as a representative candidate of the class of 2D materials, colloidal CdSe NPLs constitute a significant platform for the fundamental research and development of the next generation of optical devices. Knowledge of the spectral tunability and self‐assembly methods of CdSe NPLs could facilitate the research of other novel cadmium‐free solution‐processed 2D materials such as ZnTe, [ 165 ] ZnSe, [ 166 ] HgTe, [ 116 ] and ZnS [ 167 ] NPLs. For example, the emission peak wavelength has been tuned discretely from 345 to 380 nm in the case of ZnSe NPLs by modulating the vertical thickness over the NPL ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the MSCs that display sharp optical absorption singlets, [3–15, 18–26] there is another type of nanospecies that exhibits sharp optical absorption doublets [16, 17, 27–44] . An example semiconductor is photoluminescent (PL) CdSe peaking at around 373/393 (Species‐393) or 433/460 nm (Species‐460) [16, 27–30] .…”
Section: Introductionmentioning
confidence: 99%
“…[23] Such a possibility of wide range of applications led to several experiments for the synthesis of various ZnTe nanostructures such as quantumdots, nanoplates, thin films, nanowires, nanoribbons, and nanotubes. [24][25][26][27][28][29][30][31][32] For example, Zarei et al [33] synthesized ZnTe thin films by glancing angle technique and observed that they were useful in optoelectronic devices. In a study, Das et al [34] synthesized various ZnTe nanoparticles and reported their size-dependent structural, optical, and vibrational properties.…”
Section: Introductionmentioning
confidence: 99%